The Polish United Workers’ Party in Brudzeń Duży in the years 1972–1986 - Szymański, Andrzej (The Opole Studies in Administration and Law, 2016)
In this text, the author presents the functioning of the Commune Committee of the Polish United Workers’ Party in Brudzń Duży, a commune lying near Płock, in the years 1972–1986. It is mainly the minutes of meetings of the commune party authorities, which were analyzed, paying special attention to their reaction towards the challenge of daily life in the period before – during – and after the political breakthrough in 1981. On the basis of the analysis of the source materials, heavy ideologization of thinking of the management staff of the Municipal Committee was found and in consequence – incapacity to respond to social expectations. Hence, it led to a collapse of the influence of the Polish United Workers’ Party all over the country and then – to the liquidation of the entire political formation.